POLIURETAN MINYAK AMPAS KOPI ARABIKA ( Coffea arabica L.) - Indra Masmur; Jumadi Septian Sihombing; Mimpin Ginting (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2021)
Polymerization of coffee grounds oil with Diphenyl Methane 4,4 Diisocyanate (MDI), epoxidation with performic acid and H2SO4(p) catalyst at 40-45°C, followed by hydrolysis to obtain polyols. The synthesis was carried out by reacting the polyol with Diphenyl Methane 4,4 Diisocyanate (MDI) with a ratio (polyol: MDI) 9:1; 8:2 ; 7:3 ; 6:4 ; 5:5 (v/v) in dichloromethane solvent. Each was characterized and the density values were 0.9086 gr/cm to 0.4979 gr/cm-1, the tensile strength and elongation values were 0.113 Mpa to 0.299 Mpa and 3.23% to 6.85%, respectively.